Kajian Pemanenan Air Hujan Sebagai Alternatif Pemenuhan Air Baku Di Kecamatan Bengkalis - Yogi Septian Malik; Imam Suprayogi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Providing clean water is a major concern, because water is a basic need and is essential for life and health of mankind. Sourced from the Long Term Development Plan (RPJP) Riau Province 2005-2025 that meet the needs of clean water for domestic Riau Province large part still rely on shallow groundwater and service of the Regional Water Company (PDAM). Rainwater is a source of high quality water which is available every rainy season and has the potential to reduce the pressure on the use of fresh water resources (fresh water sources). Rainwater coming from the roof of the house is usually the cleanest water alternatives that can be used as a source of clean water one of them in the District of Bengkalis. This study aims to find out alternative clean water that can be used in the District of Bengkalis and determine the volume of rain water storage and rainwater harvesting design plan or Rainwater Harvesting. In this research, modeling Rain Cycle 2 is a rainwater harvesting modeling that uses some of the data, the data are derived from primary data in the form of extensive data roofs society, data on the number of family members in the head of the family, and the data of showers field. The results of this study rainwater harvesting by using a holding tank depends on the ability of people in the District Bengkalis income as well as extensive holdings community yard individual scale to meet the needs of clean water which ensures the availability of supply of clean water with a limited number of tanks.Keywords : Rain water harvesting , Rain Cycle 2 , raw water